Atomistic insights into the effects of carbonyl oxygens in functionalized graphene nanopores on Ca2+/Na+ sieving. (30th August 2020) - Zhao, Nana; Deng, Jiawei; Zhu, Yudan; Chen, Yaojia; Qin, Yao; Ruan, Yang; Zhang, Yumeng; Gao, Qingwei; Lu, Xiaohua
Abstract: Residual Ca 2+ decreases the efficiency and increases the power consumption of the chlor-alkali industry. However, Ca 2+ and Na + sieving is challenging due to the similar ionic radii of these cations. Inspired by the presence of carbonyl oxygens in key selective filters of biological Ca 2+ and Na + channels, we used molecular dynamics to investigate the effects of carbonyl oxygen atoms in modified graphene nanopores of various sizes (characteristic diameters: 0.57–1.50 nm) on Ca 2+ /Na + sieving. The results demonstrated that selectivity is closely associated with the different roles of the carbonyl oxygen atoms. In small nanopores, Ca 2+ sheds increased numbers of water molecules due to the predominant steric effect of carbonyl oxygen atoms. Thus, Ca 2+ must overcome a higher energy barrier than Na + . This requirement prevents the passage of Ca 2+ . In large nanopores, carbonyl oxygen atoms do preferentially substitute water molecules outside the first hydration shell of Ca 2+ compared with those outside the first hydration shell of Na +, thereby hindering Na + departure from the nanopore. These findings provide useful guidance for the further development of Ca 2+ separation materials as sensors and ion separators. Graphical abstract: Image 1